The Relationship Between The Management Of Emotional Intelligence And The Implementation Of Leadership Education And Training For Senior High School Principals - Djafri, Novianty; Rahmat, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Leadership training is able to improve the emotional intelligence of school principals. A good-trained emotion can lead to wise actions and professional thoughts, attitudes, personalities, and behaviors in performing principals’ competencies. The Principal Leadership Training is analyzed through several indicators, including the techniques and output of the Education and Training implementation; meanwhile, the professional competencies managed by the leaders in emotional intelligence are self-awareness, self-management, motivation, social awareness, and peer relation management. The purpose of this study is to examine the relationship between the management of emotional intelligence and the implementation of leadership education and training for senior high school principals in Gorontalo Province. It employed a survey method and quantitative descriptive approach aiming at obtaining a description of principals’ emotional intelligence in leadership. The respondents were selected by using the purposive sampling technique. Further, the data were collected from observation (to directly observe the research area/the object) and questionnaire/test (to find out principals’ emotional intelligence management through IQ test, personality test, EQ and competence test of principals’ leadership); they were analyzed by doing a percentage calculation % = F/N x 100 (actual and ideal scores)